Netraspoon: Inovasi sendok makan ergonomis berindikator suhu untuk mendukung kemandirian anak tunanetra - Wicaksono, Gregorius Guntur Jembar; Ramadhani, Alya; Anggraheni, Sinta Nur; Sutjiadi, Corinthia Gabrielle; Enoch, Arethusa Guinevere Dova; Mutmainah, Baridah (Institut Seni Indonesia Yogyakarta, 2025)
Netraspoon is an innovative eating utensil designed for blind children aged 6–15 years, aimed at enhancing independence and safety. The spoon is equipped with a temperature sensor and vibration indicator that alerts the user when the food reaches 50 degrees Celsius. The study employed a design thinking approach involving 20 blind children and educators from special needs schools and blind foundations in Jakarta and Yogyakarta as participants. The development process went through the stages of empathize, define, ideate, prototype, and test. Trial results showed that Netraspoon is easy to use, comfortable to hold, and helps blind children recognize hot food temperatures, thereby reducing the risk of mouth injury. Its ergonomic design with a 90-degree angle and food-grade materials supports product safety and comfort. This innovation provides an effective solution to support the independence of blind children in Indonesia.